2003
DOI: 10.1021/nl025926e
|View full text |Cite
|
Sign up to set email alerts
|

Purity Evaluation of As-Prepared Single-Walled Carbon Nanotube Soot by Use of Solution-Phase Near-IR Spectroscopy

Abstract: We report a rapid, quantitative procedure for the evaluation of the carbonaceous purity of bulk quantities of as-prepared single-walled carbon nanotube (SWNT) soot by the utilization of solution-phase near-IR spectroscopy. The procedure starts with two steps of homogenization followed by solution/dispersion spectroscopy of a representative part of the bulk sample. The purity is evaluated against a reference sample by utilizing the region of the second interband transition (S 22 ) for semiconducting SWNTs. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
429
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(439 citation statements)
references
References 40 publications
(110 reference statements)
8
429
0
Order By: Relevance
“…For a given absorption spectrum of SWCNTs, it has been shown that well-resolved features mean the fraction of individual SWCNTs is higher [29]. The I MAX -to-FWHM ratio has been proven to be related to the degree of SWCNT debundling and aggregation, which is used to evaluate the purity of SWCNT samples [31][32]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For a given absorption spectrum of SWCNTs, it has been shown that well-resolved features mean the fraction of individual SWCNTs is higher [29]. The I MAX -to-FWHM ratio has been proven to be related to the degree of SWCNT debundling and aggregation, which is used to evaluate the purity of SWCNT samples [31][32]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Following the initial release of a trace amount of Ni, there is no detectable release and thus no indication of significant oxidative attack on the covering carbon shells for two months. ** Carbonaceous purity is defined in the literature as the mass ratio of pure SWCNT to the total carbonaceous material and it is evaluated by near-IR spectroscopy against a reference sample [31].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Haddon et al [29] proposed a spectroscopic approach to quantitatively evaluate the purity of SWNTs. We attempt to apply this method to estimate the purity of the shortened SWNTs.…”
Section: Shortened Carbolex Swntsmentioning
confidence: 99%
“…Though a 100% pure SWNT sample is unavailable, we could estimate the purity of our functionalized full-length SWNTs with respect to the reference sample R2 in Ref. [29], which is an 'impurity-free' fragment of soot directly from the arc chamber. By referencing to the documented datum A(S 22 ,R2)/A(T,R2)Z0.141, we could conclude that the relative purity of our functionalized shortened SWNTs is 129% (0.1818/0.141).…”
Section: Shortened Carbolex Swntsmentioning
confidence: 99%
See 1 more Smart Citation